R&D Investments, EPO Patent Applications and the Economic Heterogeneity within the EU - Zuzana Potužáková; Jan Öhm (Review of Economic Perspectives, 2018)
In addition to internationalization and growing volumes of international trade in goods, the importance of expenditure on research and development (R&D) has grown significantly. National patent protection has become rather insufficient with increased international trade in goods, which has resulted in the importance of the international patent protection. The main aim of the article is to analyse the relation between R&D investment and the number of patent applications filed with the European Patent Office (EPO) after the year 2000, when the EU`s Lisbon Strategy was launched. The authors have focused primarily on the differences among the EU macro-regions, which are based on the socioeconomic models. Conclusions imply that one percentage point of R&D expenditure generates roughly 100 EPO applications and the findings also show that individual macro-regions have the identical scattered data. However, dispersions in the individual groups of the EU Member States after the year 2000 differ. The EU Member States are starting to vary significantly in the intensity of R&D support also within each macro-region, thus disparities increase within the EU. Therefore, the attitude to GERD is considered to be an important factor contributing to the greater economic disparities within the EU.
Keywords: 330; EU; EPO application; economic growth; GERD internationalization; R&D